The Differences in English Learning Outcomes Using Flashcards and 'Snake-Ladder' Game Learning Media in Elementary School - Nurhafifah Nurhafifah; Naeklan Simbolon; Try Wahyun Purnomo (FIP Unimed, 2021)
This study was to determine the differences in learning outcomes of English using Flashcards and Snake and Ladders learning media in elementary schools. This research is a type of comparative research using a quasi-experimental research design. This research was conducted at Tanjung Balai State Elementary School using two classes. Test the instrument by testing the validity and reliability. Hypothesis testing using t-test, obtained tcount > ttable (6.63 > 2.00), with a significant level = 0.05. The results of this study indicate that there are differences in English learning outcomes between students who are taught using Flashcards as learning media. taught using snake and ladder learning media, fourth grade elementary school students.Keywords: Learning Outcomes, media, Flashcards, Snake and ladders game , English